2018
DOI: 10.3390/geosciences8100358
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Holocene Mercury Accumulation Trends by Combining Palynological and Geochemical Records of Lake Sediments (Black Forest, Germany)

Abstract: Forest vegetation plays a key role in the cycling of mercury (Hg) and organic matter (OM) in terrestrial ecosystems. Litterfall has been indicated as the major transport vector of atmospheric Hg to forest soils, which is eventually transported and stored in the sediments of forest lakes. Hence, it is important to understand how changes in forest vegetation affect Hg in soil and its biogeochemical cycling in lake systems. We investigated the pollen records and the geochemical compositions of sediments from two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 91 publications
(129 reference statements)
1
4
1
Order By: Relevance
“…Joo et al, based on the δ 13 C org in the JM05 core, suggested that a large proportion of TOC is allochthonous, reflecting TOC derived from the terrestrial environment rather than those produced within the fjord. The absence of significant positive relationships between THg and TOC in both sediment cores (JM05; r 2 < 0.01, HH12; r 2 = 0.20, both p > 0.05) is in contrast with many previous studies, which observed significant relationships in lakes, , lacustrine, and marine sediment cores spanning the Holocene. It is possible that, while TOC is derived from the terrestrial environment, Hg may have originated from a different source.…”
Section: Resultscontrasting
confidence: 82%
“…Joo et al, based on the δ 13 C org in the JM05 core, suggested that a large proportion of TOC is allochthonous, reflecting TOC derived from the terrestrial environment rather than those produced within the fjord. The absence of significant positive relationships between THg and TOC in both sediment cores (JM05; r 2 < 0.01, HH12; r 2 = 0.20, both p > 0.05) is in contrast with many previous studies, which observed significant relationships in lakes, , lacustrine, and marine sediment cores spanning the Holocene. It is possible that, while TOC is derived from the terrestrial environment, Hg may have originated from a different source.…”
Section: Resultscontrasting
confidence: 82%
“…S3), which is consistent with the higher concentration of chlorine in the water phase, which may be attributed to the use of road salt during winter (Supporting Information Table S4). However, notable concentrations of copper were also observed in a sediment trap of the Black Forest, which is consistent with the geochemical signals found in the lake sediment of medieval mining activities near the lake catchments (Schütze et al 2018).…”
Section: Chemical Composition Of Trap Materialssupporting
confidence: 84%
“…Similarly, a higher percentage of peatlands in the catchment is related to both higher DOM and higher Hg concentrations in lake water (Laudon et al 2004;Wiener et al 2006). Previous studies on Holocene palynological and geochemical data derived from lake sediments indicate a significant increase in Hg concentrations when catchment vegetation shifted from deciduous to coniferous vegetation during the Holocene (Rydberg et al 2015;Schütze et al 2018).…”
mentioning
confidence: 89%
“…Comparison of Honnamanakere Lake sediment core heavy metal content (ppm) with other Indian lakes.The Hg content in Tibetan lakes(Yang et al, 2010) and Black Forest, Germany(Schütze et al, 2018) was found higher than the HKL sediments. Zn and Pb content in lake sediment cores of the Mongolian Plateau (Wan et al, 2019) were found to be lower than the HKL sediments.…”
mentioning
confidence: 73%